(3cJGH GdeYhfI aj Yde GdMSGH GdghGFis - (3CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,TgGH GdOjf, J (B815 (3g` s ((3eUWai Hf jhSa Hf SdjeGf GdUahQi HdOkG GdbGOQi WQjbI s)
(3ChdgG (B:s
(3GdMeO ddg YOO fYeGFg CeG HYO agPg QSGdI ai Yde GdMSGH bO CdaJgG dHYV GdENhGf GdebOeI ajgG eSGFd GdChdi ai JYQja GdMSGH s
(3BNQgG (B:s
(3aELeY LejY GdLed hCbSe eLehYgG Ydi YOI MQha GdGSe GdeVeQ GdG hGMO aeG NQL agh LedI MQha GdGSe hdjcf gPG BNQ GdeYhfI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
Keywords: (3GdQjGVjGJs